Comparison of certain radiomorphometric facial indices in different facial types of Iraqi adults using Cone Beam Computed Tomography - Ali, Zahraa R.; Mahmood, Abeer B.; Al Nakib, Lamia H.; Muhamed Ali, Maisaa Q. (Journal of Baghdad College of Dentistry, 2018)
Background: The human face has its special characteristics. It may be categorized into essentially three kinds in horizontal and vertical directions: short or brachyfacial, medium or mesofacial and long or dolichofacial. The aim of this study was to describe several orofacial indices and proportions of adults, according to gender in Iraqi subjects by using cone beam computed tomography . materials and methods: This prospective study included 100 Iraqi patients (males and females) ranging from 20 to 40 years. All subjects attended the Oral and Maxillofacial Radiology Department of Health Specialist Center for Dentistry in AL Sadr city in Baghdad taking cone beam computed tomography scan for different diagnostic purposes from October 2016 to May 2017. The facial index was used for determination of facial type. Subjects were divided according to gender and then by photoshope cs4 programe ,five variables were calculated : inferior face index, superior face index, chin-face proportion, chin proportion and mandibular proportion. Results: The average values obtained from the subjects divided according to genders that presented significant diffeÂ¬rences were: inferior face index and superior face index for males and inferior face index, superior face index and mandibular proportion for females. Conclusion: There were variation in some indices and proportions according to genders. In males groupe, inferior face index and superior face index had significant difference between the average of the facial types, while in female group, inferior face index, superior face index and mandibular proportion had significant difference between the average of the facial types